Utveckling av en informationsportal för svensk tillverkningsindustri: Fallstudie av en leverantörskedja - Ahmad, Koiar; Almasri, Obadah; Ferm, Robin; Johansson, Emelie; Sheik, Sally; Vertetics, Oskar (My University, 2020)
This bachelor thesis is dealing with the conceptual development process of an interorganizational information portal for supply chains based on a specific case study, consisting of three companies. There is a need to create a clearer understanding of what the digitalization within the manufacturing industry really means, how it can be utilized and what profits it can create for various businesses. Thus, in addition, it will also berclarified what beneficial values such a platform can provide to make a potential investment more transparent. Interviews with selected representatives from the concerned companies were carried out to identify the needs and scope, which resulted in a specification of requirements for an information portal. This was then used to produce a concept to be presented for the parties involved, to get feedback and be able to gather beneficial and challenging aspects for the potential future use of an information portal. Mainly, the use of an information portal of this type will save time by gathering more comprehensive data and information at the same place. Furthermore, the information portal will lead to better transparency between suppliers and customers, while also providing positive effects to productivity, flexibility and quality.
Keywords: supplier portal, IOIS, supply chain, industry 4.0, smart manufacturing; information portal